2022
DOI: 10.18619/2072-9146-2022-1-79-85
|View full text |Cite
|
Sign up to set email alerts
|

Potato viruses of 7 commercial cultivars grown in field Primorsky Krai of Russia

Abstract: Scientific relevance. Plant viruses cause a significant economic loss to potato production, especially if plants are infected at early growth stages and infections are mixed. Viral diseases reduce both yield and quality of harvested crops. Detection and identification of plant viruses are key important to prevent their spreading and to achieve potential yield predetermined by characteristics of varieties.Research methods. Seven potato varieties, bred in Russia and overseas, were used in the field experiment: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…All of the symptoms were distinct on potato plants and demonstrated the accumulation of plant viruses (Fig. 2) [33]. In our previous studies, we found that the distribution of plant viruses among the studied varieties was uneven.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…All of the symptoms were distinct on potato plants and demonstrated the accumulation of plant viruses (Fig. 2) [33]. In our previous studies, we found that the distribution of plant viruses among the studied varieties was uneven.…”
Section: Resultsmentioning
confidence: 66%
“…During the years of research, the species composition of viruses did not change significantly. The manifestation of symptoms depended on both the amount and composition of the viral infection [33]. For example, a high concentration of PVX in plants of potato variety Laperla with an equal proportion of all other viruses lead to the development of chlorosis along leaf edges, the necrosis and deformation of leaves, dwarf forms, and mottles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations